The Impact of Transition of Small Medium Enterprises (SMEs) Businesses into an Online Digital Marketing System in Nigeria - Bem, Samuel Angwe; Matthew, Ugochukwu Okwudili; Ndukwu, Charles Chukwuebuka; Ebong, Godwin Nse (Recent Research Reviews Journal, 2023)
In every customer oriented business enterprise, digital marketing is at the forefront of every inventive product campaign. Businesses have continued to place a high priority on the need to grow their customer base, product rebranding and revenue projection by implementing efficient digital marketing strategies. This approach will require technological developments such as the use of digitization and social media enablement that will promote businesses to disseminate information and connect wide spectrum of customers across divide. The purpose of this study is to examine the value and impact of digital marketing on the competitive participation of small and medium-sized businesses in the Nigeria. The study explains why adopting digital marketing is essential for small and medium businesses to take advantage of customer’s digital potency and influence their needs to shape the market through digital activation. A sample of 220 respondents were taken from the total population of 250 small ,medium enterprises within the study area using random sampling method in which approximately 88% of the administered questionnaires were retrieved and found useful for the data analysis. The research finding indicated that after adopting digital marketing, the most number of SMEs (36%) earn between 1 and 3 million Naira as a turn-over higher than the previous year when there was no implementation of digital marketing mechanization.
Keywords: SMEs; Digital Marketing; ICT; Social Media Platform; Online Marketing; digital media